Famous Leaders - Andrew Langley (Oxford, United Kingdom Capstone Global Library Ltd, 2017)
Why is Elizabeth I considered one of the England's greatest rulers? How did Mahatma Ghandi bring peace to India? What impact did Martin Luther King, Jr. have on American civil rights? Get ready to meet famous leaders whose ideas and actions have determined the course of history.
Keywords: PY-UOI - Who We Are - G-5 - Role Models -- PY-UOI - Who We Are - G-5 - Role Models